A Comparative Study on UHPLC-HRMS Profiles and Biological Activities of Inula sarana Different Extracts and Its Beta-Cyclodextrin Complex: Effective Insights for Novel Applications - Gokhan Zengin; Nilofar; Evren Yildiztugay; Abdelhakim Bouyahya; Halit Cavusoglu; Reneta Gevrenova; Dimitrina Zheleva-Dimitrova (MDPI AG, 2023)
Within this particular framework, the extracts obtained from Inula sarana using a variety of solvents, included n-hexane, ethyl acetate, dichloromethane (DCM), 70% ethanol, ethanol, and water. The extracts obtained from n-hexane, ethyl acetate, and DCM were then subjected to a specific method for their incorporation into β-cyclodextrin (β-CD). The establishment of complex formation was validated through the utilization of scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The identification of phytochemical components was executed using UHPLC-HRMS. Furthermore, the total phenolic and flavonoid content was evaluated using the Folin-Ciocalteu assay and the AlCl3 method. Subsequently, the determination of antioxidant capacity was conducted utilizing DPPH, ABTS, CUPRAC, Frap, PBD, and MCA assays. The enzyme inhibitory activities of the samples (extracts and β-CD complexes) were also examined by AChE, BChE, tyrosinase, α-glucosidase, and α-amylase. The findings indicated that water and 70% ethanol extracts contained the highest phenolic content. One hundred and fourteen bioactive compounds were identified by UHPLC-HRMS analysis. This study unveiled a substantial array of flavonoids, phenolic acid-hexosides and caffeoylhexaric acids within I. sarana, marking their initial identification in this context. Among the various extracts tested, the 70% ethanol extract stood out due to its high flavonoid content (jaceosidin, cirsiliol, and eupatilin) and hydroxybenzoic and hydroxycinnamic acid hexosides. This extract also displayed notably enhanced antioxidant activity, with ABTS, CUPRAC, and FRAP test values of 106.50 mg TE/g dry extract, 224.31 mg TE/g dry extract, and 110.40 mg TE/g, respectively. However, the antioxidant values of the complex extracts with β-CD were generally lower than those of the pure extracts, an observation warranting significant consideration. In terms of enzyme inhibition activity, the ethanol and 70% ethanol extracts exhibited higher inhibitory effects on AChE, tyrosinase, and α-glucosidase. Conversely, n-hexane displayed stronger inhibitory activity against BChE. The ethyl acetate extract demonstrated elevated amylase inhibitory activity. However, the antioxidant values of the complex extracts with β-CD were generally lower than those of the pure extracts, a noteworthy observation, while water and extracts from the I. sarana complex with β-CD exhibited minimal or negatable inhibitory activity against specific enzymes.